1996
DOI: 10.1243/pime_proc_1996_210_045_02
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Face Type Magnetic Couplers

Abstract: A theoretical analysis of magnetic couplers is recounted, leading to the design and manufacture of prototype disc type magnetic couplers. Design and development of experimental test rigs are also given. Test results are presented and compared with theoretical calculations. This shows very good agreement. The exception to the rule was the case of axial load measurements, which were not accurately evaluated by the computations. The geometries tested here showed the optimum design to consist of rotors with eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…For practical applications it is also important to consider the significant axial force between the two discs. This is studied, e.g., in [24,30,33,34] and there it is shown that the force is maximum at zero torque and vice versa. This can be used to convert a rotation into an axial vibration (e.g., for dynamic vibration absorbers or for a lock that is opened by a magnetic key).…”
Section: Resultsmentioning
confidence: 99%
“…For practical applications it is also important to consider the significant axial force between the two discs. This is studied, e.g., in [24,30,33,34] and there it is shown that the force is maximum at zero torque and vice versa. This can be used to convert a rotation into an axial vibration (e.g., for dynamic vibration absorbers or for a lock that is opened by a magnetic key).…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, there are two types of analytical modeling for magnetic actuator: -3D Modeling is based on Amperien model using Biot-Savart law or on Coulombian model using charge surfaces [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. These methods can be used only in free space without ferromagnetic material.…”
Section: Soft-iron Yokementioning
confidence: 99%
“…There are two main types of magnetic couplings: synchronous and asynchronous (eddycurrent), with radial and axial flux topologies. The synchronous magnetic coupling [1][2][3][4][5] consists of rare-earth permanent magnets (PMs) placed on both rotors that move at the same speed. It has a pull-out torque, which is the maximum torque that can be transmitted by the coupling before the stall.…”
Section: Introductionmentioning
confidence: 99%